Effects of Rural Roads for Improving Road Traffic Safety in Bangladesh (Indian Journal of Transport Engineering (IJTE), 2024)
Road Traffic crashes not only claim active lives and inflict injuries but also create an economic burden on society through the loss of productivity of the killed or injured persons. The problem of deaths and injuries as a result of road traffic crashes is now acknowledged to be a global public health problem all over the world, especially in low-and middle-income countries like Bangladesh. However, the state of road traffic crashes in a developing country is much worse compared with that of developed countries. For better planning, improvement, maintenance and operations, the total road systems in Bangladesh are assigned primarily to the Roads and Highways Department (RHD) and the Local Government Engineering Department (LGED) which are called rural roads. However, road traffic safety depends on the reduction of road traffic crashes on RHD road networks and simultaneously LGED road networks. However, the key activities taken by the Government for improving road traffic crashes mainly for the road networks belonging to the RHD leaving a huge volume of rural roads. Moreover, the present recording and reporting systems of road traffic crashes are based on the RHD networks leaving the rural roads. Therefore, the actual state of road traffic safety on rural roads is unknown and the present state of road traffic safety in this country is underreporting. So, it is necessary to identify the effects of rural roads for improving the total traffic safety of the country. Since rural roads have no specific traffic crash data and the volume of rural roads is significantly high, it is impossible to consider all the rural roads to evaluate the state of traffic safety. The research was performed by assessing the traffic safety of randomly selected 8 rural roads from each of the country's divisions representing the country's demographic and topographic characteristics through Road Safety Inspection (RSI). The primary and secondary data for this research were collected by road inspections and from the Accident Research Institute (ARI) of Bangladesh University of Engineering and Technology (BUET), RHD, LGED and different publications.